90Y‐ibritumomab tiuxetan radiotherapy as first‐line therapy for early stage low‐grade B‐cell lymphomas, including bulky disease. (8th July 2014) - Samaniego, Felipe; Berkova, Zuzana; Romaguera, Jorge E.; Fowler, Nathan; Fanale, Michelle A.; Pro, Barbara; Shah, Jatin J.; McLaughlin, Peter; Sehgal, Lalit; Selvaraj, Vijairam; Braun, Frank K.; Mathur, Rohit; et al.
Summary 90Y‐ibritumomab‐tiuxetan (90YIT) was used as a first‐line therapy for patients with early‐stage follicular lymphoma (FL) or marginal zone B‐cell lymphoma (MZL). Thirty‐one patients were treated, with an overall 3‐month response rate of 100% (68% complete response, 29% unconfirmed complete response and 3% partial response). At a median follow‐up of 56 months, ten patients (32%) had disease relapse or progression. The progression‐free rates at 3 and 5 years were lower in males, patients with FL, stage II diseaseand non‐bulky disease, although they did not reach statistical significance. Grade 3–4 neutropenia, thrombocytopenia and anaemia were 61%, 35%, and 3%, respectively. 90YIT was well tolerated, including in those patients over 60 years old, and achieved high response rates in patients with early‐stage low‐grade B‐cell lymphomas. Bulky disease did not adversely affect tumour response.